Cyborg work: borders as simulation - Lalonde, Patrick C. (The British journal of criminology, 2018)
Much recent research has focused on examining various binary contradictions and employing metaphors pertaining to border security. Ultimately, this article argues that existing debates and metaphors are inadequate in describing what is understood and agreed upon in the literature in terms of borders. This article proposes a refinement of existing theory for contemporary borders, employing Baudrillard’s concept of ‘simulation’. The metaphor of the ‘simulated border’ functions to avoid debates surrounding geospatiality while also incorporating aspects of risk society and control in concluding that borders are anything but organic security environments, with the ‘stretched screens’ of border agents serving to produce dividuals that are tested within games of security to govern mobility anywhere in time or space.